A numerical analysis of electric field strength over planar microarray dot electrode for dielectrophoretic lab-on-chip device - Yafouz, Bashar; Kadri, Nahrizul Adib; Ibrahim, Fatimah (2012)
Dielectrophoresis (DEP) has been proven as a method of manipulating and analyzing the electrophysiological properties of bioparticles by applying non-uniform electric fields generated through special electrodes. Various electrode geometries have been developed to address different applications. Simulation of the electric field strength over electrodes is essential in order to optimize the generated DEP force for enhancing cell manipulation. This paper describes the study of electric field distribution over planar multiple microarray dot electrode using numerical modeling of Comsol Multiphysics 4.2aÂ®. Results show that the electric field strength is axisymmetrical around the centre of the dot aperture and that is higher at the dot edges than the dot centers. Further studies will be conducted to investigate the effect of applying different frequencies, varying dots size and adding ground plane in between the electrode dots. Â© 2012 IEEE.